Hybrid compounds: from simple combinations to nanomachines - Mueller-Schiffmann, Andreas; Sticht, Heinrich; Korth, Carsten (Biodrugs, 2012)
The combination of two different and independently acting compounds into one covalently linked hybrid compound can convey synergy from the effects of both independently acting moieties to the new composite compound, leading to a pharmacological potency greater than the sum of each individual moiety's potencies. Here, we review a variety of such hybrid compounds, which can consist of various functional parts, molecular recognition or subcellular targeting moieties, or combinations thereof, acting either simultaneously or sequentially. Such moieties within a hybrid compound can consist of a variety of substance classes, including small organic molecules, polypeptides or nucleic acids identified either via rational molecular design or selection from libraries. Precedent for hybrid compounds comes from naturally occurring proteins and small molecules, such as botulinum toxin and bleomycin, which are secreted by micro-organisms. We review the high degree of suitability of hybrid compounds for the treatment of multifactorial diseases by simultaneously hitting several targets along an identified disease pathway. Examples are hybrid compounds against Alzheimer's disease, against the cancer-relevant phosphoinisitide-3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) and epidermal growth factor signaling cascade, or in antimalarial therapy via simultaneous hitting of different mechanisms of hemozoin formation. Molecular recognition by peptides or aptamers (recognition-specific RNA or peptide sequences) can be combined with the transport of small molecule ?-sheet breakers or toxins, or targeting to ubiquitin-dependent proteolysis. The vision of molecular nanomachines is currently realized in sequentially acting modular nanotransporters, consisting of four modules including a target, a membrane and nuclear translocation sequence, as well as a drug attachment domain. Through the rational combination of existing drugs and the synergy of their effects, a rapid amplification of their potency may be achieved, greatly accelerating drug development. A further enhancement of simultaneous multitarget action is enabled through the design of multifunctional hybrid drugs with sequential effects that make these hybrid molecules resemble intelligent nanomachines.
EVALuna2:26273